Effectiveness of Protective Media Applying for Long-Term Storage of the Rabies Virus L. Pasteur Strain at Various Low Temperatures - Varianytsia , Viktoriia; Vysekantsev , Igor (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 283